The Eart’S Rotation Axis And The Moon‘S Orbit - Ciobanu, Monica Zoe (European Journal of Applied Sciences, 2024)
In the XX century the diminution of the obliquity of the ecliptic came to be recognised as a certitude. This paper presents only a possible supposition regarding the connection of this astronomical phenomenon with the forces acting on the Moon, and on the Earth’s rotation axis.